2023
DOI: 10.1136/bmjment-2023-300665
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance, age and depression’s impact on cognition in middle-aged adults from the PREVENT cohort

Abstract: BackgroundAlzheimer’s disease (AD), type 2 diabetes mellitus (characterised by insulin resistance) and depression are significant challenges facing public health. Research has demonstrated common comorbidities among these three conditions, typically focusing on two of them at a time.ObjectiveThe goal of this study, however, was to assess the inter-relationships between the three conditions, focusing on mid-life (defined as age 40–59) risk before the emergence of dementia caused by AD.MethodsIn the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, in a cross-sectional study of Chinese MDD subjects it was noted, that IR was associated with increased likelihood of suicide attempts [ 15 ]. What is more, a cross-sectional study in middle-aged subjects showed, that higher IR was not only a predictor of higher depressive symptoms but also worse executive functions [ 16 ▪ ].…”
Section: Metabolic Subtype Of Depressionmentioning
confidence: 99%
“…Furthermore, in a cross-sectional study of Chinese MDD subjects it was noted, that IR was associated with increased likelihood of suicide attempts [ 15 ]. What is more, a cross-sectional study in middle-aged subjects showed, that higher IR was not only a predictor of higher depressive symptoms but also worse executive functions [ 16 ▪ ].…”
Section: Metabolic Subtype Of Depressionmentioning
confidence: 99%